Geographic filling delay of the choriocapillaris in the region of dilated asymmetric vortex veins in central serous chorioretinopathy. - Shoji Kishi; Hidetaka Matsumoto; Shozo Sonoda; Takashi Hiroe; Taiji Sakamoto; Hideo Akiyama (PLoS ONE, 2018)
PURPOSE:To investigate the correlation between geographic filling delays in the choriocapillaris using indocyanine green angiography (ICGA) images and dilated vortex veins in central serous chorioretinopathy (CSC). DESIGN:Observational case series. PARTICIPANTS:Thirty-two eyes of 32 patients, 21 with acute and 11 with chronic CSC. METHODS:Digital ICGA and fluorescein angiography (FA), with videoangiography, and swept-source optical coherence tomography (SS-OCT) for B-scan and en-face choroidal imaging were performed. Overlapping of the filling delay areas in the choriocapillaris in the early-phase ICGA images and the region of dilated vortex veins in the en-face images were analyzed. The consistency of both areas was graded as follows. Grade 3: filling delay area is entirely involved in the dilated vortex vein region. Grade 2: 50% or more of filling delay area overlaps with the dilated vortex vein region. Grade 1: less than 50% of filling delay area overlaps with the dilated vortex vein region. Grade 0: no tendency for overlapping of two areas. We evaluated the asymmetry of upper and lower vortex veins in en-face images of the Haller layer. Using the binarization method, we quantified the luminal and stromal areas of the choroid. The ratios of the Haller layer area and luminal areas in the Haller layer to total choroidal area were examined. RESULTS:The consistency of overlapping of the two areas was grade 2.62 ± 0.49 in acute CSC and grade 1.55 ± 0.78 in chronic CSC (p = 0.0005). Asymmetry of upper and lower vortex veins was seen in 17 of 22 eyes (81%) with acute CSC and 6 of 11 eyes (54.5%) with chronic CSC (p = 0.114). Central choroidal thickness was 411 ± 79 μm in acute CSC and 326 ± 64 μm in chronic CSC (p = 0.004). In the posterior fundus with a 4500 μm diameter, the ratio of the Haller layer area to total choroidal area was 63.7 ± 8.6% in acute CSC and 57.1 ± 7.9% in chronic CSC (p = 0.047). The ratio of the luminal area in the Haller layer area to total choroidal area was 46.9 ± 7.6% in acute CSC and 40.0 ± 6.9% in chronic CSC (p = 0.014). CONCLUSION:Filling delay areas in the choriocapillaris and dilated vortex vein regions showed marked overlapping in acute CSC. Increased choroidal thickness was attributed to dilated vortex veins. These findings suggest that the blood flow into the choriocapillaris is delayed as a result of congestion of the dominant vortex veins that supply this geographic area. CSC may be a disease characterized by vortex vein congestion that develops in eyes with asymmetric vortex veins.